Tasmim Ta‘lim Al-lughah Al-‘Arabiyya: Fahm Al-Jawhar wa Istiratijiyat At-Tadris Al-fa‘alah - azizah, walaa; Sari, Dyah Madia Puspita; Yuliana, Eka (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2025)
Arabic language education plays a vital role in preserving cultural heritage and enhancing cross-cultural communication, yet challenges remain in designing effective teaching methods that align with modern advancements. Purpose: This study aims to understand the essence of Arabic language learning and formulate effective, innovative, and adaptive teaching strategies suited to contemporary educational needs. Methodologies: The methodology employs a literature review and comparative analysis of Arabic teaching literature combined with a study of current technological and pedagogical approaches that improve learning quality. Principal Results: The study reveals that successful Arabic education relies heavily on integrating cultural elements into the curriculum, utilizing technology to create interactive learning environments, and continuous teacher training. Ongoing assessment plays a crucial role in adapting teaching strategies to consistently enhance education quality. Major Conclusions: The integration of cultural aspects, educational technology, teacher development, and continuous evaluation are key to effective and adaptive Arabic teaching strategies. Contributions to the Field: This research contributes a comprehensive Arabic language learning model that blends theory and practice, serving as a guide for future curriculum development and instructional strategies. Furthermore, it encourages the adoption of more dynamic and responsive approaches to meet student needs and technological advances in education.